2021
DOI: 10.1111/agec.12660
|View full text |Cite
|
Sign up to set email alerts
|

Impact of climate change on global agricultural markets under different shared socioeconomic pathways

Abstract: We quantify changes in global agricultural trade by 2050 for maize, rice, soybeans, and wheat due to variations in commodity yields triggered by climate change. Our scenarios are differentiated by population levels and economic growth rates associated with three shared socioeconomic pathways. A baseline assuming no climate change is compared to a scenario consistent with a representative concentration pathway (RCP) assuming a radiative force of 8.5 W m −2 , i.e., RCP8.5. The baseline and the scenarios will est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 80 publications
1
8
0
Order By: Relevance
“…Climate change has affected major crops such as maize and soybeans, according to previous studies (Basche et al 2016 ; Dumortier et al 2021 ). An investigation by Wang et al ( 2020 ) looked at the effects of drought on maize and soybean output in China and found that drought frequency and intensity were negatively affecting the two crops.…”
Section: Introductionmentioning
confidence: 87%
“…Climate change has affected major crops such as maize and soybeans, according to previous studies (Basche et al 2016 ; Dumortier et al 2021 ). An investigation by Wang et al ( 2020 ) looked at the effects of drought on maize and soybean output in China and found that drought frequency and intensity were negatively affecting the two crops.…”
Section: Introductionmentioning
confidence: 87%
“…Although such combined studies exist at the global level considering macro regions (e.g. Nelson et al 2014, Van Meijl et al 2018, Dumortier et al 2021, respective comprehensive regional analysis is rather scarce or non-existent in the context of a large ensemble of climate change scenarios from different climate and crop models globally applied in a consistent manner. Therefore, the aim of this paper is to quantify the possible consequences of climate change for EU agriculture in 2050, considering both biophysical impacts and agricultural market interactions within a consistent modelling framework.…”
Section: Introductionmentioning
confidence: 99%
“…However, now they suffer from a negative trade balance [ 8 ]. Hence the typical difficulties of the war economy in the European area, which, between the interruption of trade relations and the sanctions decided by the international community against Russia, have generated the consequences mentioned above [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%